The Analysis of Students’ Pronunciation Error on English Diphthong Made by Fifth Semester of English Language Education Program Universitas Negeri Padang - Fatihatus Saadah; Havid Ardi (Universitas Negeri Padang, 2020)
This study aims to determine students’ pronunciation error in pronouncing English diphthong sounds made by students of English language Program Universitas Negeri Padang. This research is descriptive quantitative with 219 population. The sample of this study was 25 students chosen by various origin who were selected by using purposive sampling technique. The data were collected through pronunciation test and analyzed by using formula and the rubric score, while the students’ recordings were transcribed. The finding of this research showed that ability of students in pronouncing diphthong were fair (60.00%), good (24.00%), poor (12.00%) and very good only one students (2.00%). Therefore, it can be concluded that there are eight kinds of diphthong pronunciation error and various result of students’ ability. As the result, students need to practice more in pronouncing diphthong in order to improve their ability.